2021
DOI: 10.1038/s41398-021-01515-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between synaptic density marker SV2A, glutamate and N-acetyl aspartate levels in healthy volunteers and schizophrenia: a multimodal PET and magnetic resonance spectroscopy brain imaging study

Abstract: Glutamatergic excitotoxicity is hypothesised to underlie synaptic loss in schizophrenia pathogenesis, but it is unknown whether synaptic markers are related to glutamatergic function in vivo. Additionally, it has been proposed that N-acetyl aspartate (NAA) levels reflect neuronal integrity. Here, we investigated whether synaptic vesicle glycoprotein 2 A (SV2A) levels are related to glutamatergic markers and NAA in healthy volunteers (HV) and schizophrenia patients (SCZ). Forty volunteers (SCZ n = 18, HV n = 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 98 publications
2
40
0
Order By: Relevance
“…In addition, its concentration in white matter can reflect the development of axons. Due to NAA being located at the synaptic terminal, dendrites, and neuronal somata, its concentration may reflect the level of synapses and the ratio of NAA/Cr reflects the integrity of synapses (Onwordi et al, 2021). Our meta-analysis showed that during the pathological development from MCI to AD, the ratio of NAA/Cr in the hippocampus and PC, and the concentration of NAA in PC decreased dramatically.…”
Section: Metabolic Changes Of Neurochemicals During the Progression From MCI To Admentioning
confidence: 72%
“…In addition, its concentration in white matter can reflect the development of axons. Due to NAA being located at the synaptic terminal, dendrites, and neuronal somata, its concentration may reflect the level of synapses and the ratio of NAA/Cr reflects the integrity of synapses (Onwordi et al, 2021). Our meta-analysis showed that during the pathological development from MCI to AD, the ratio of NAA/Cr in the hippocampus and PC, and the concentration of NAA in PC decreased dramatically.…”
Section: Metabolic Changes Of Neurochemicals During the Progression From MCI To Admentioning
confidence: 72%
“…Indirect measures of synaptic loss as changes in brain functional MRI network topology have previously been associated with major disease symptoms ( 46 ). In vivo human PET imaging studies evaluating SV2A density ( 47 49 ) show reduced tissue SV2A binding and indicate that measures of cortical volume reduction ( 50 ) underestimate the extent of synaptic loss in AD. Although we observed some volume loss over the short 12- to 18-month longitudinal follow-up, we could not measure reductions of SV2A binding in the remaining brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamatergic dysfunction is an important factor in schizophrenia onset, and SV2A density and glutamate levels in anterior cingulate cortex and hippocampus have been measured in patients with schizophrenia compared to healthy volunteers with [ 11 C]UCB-J PET. Interestingly, no significant relationship was reported between [ 11 C]UCB-J binding and glutamate levels in the patients, while a positive correlation was detected in healthy control subjects ( Onwordi et al, 2021 ).…”
Section: Synaptic Vesicle Glycoprotein 2a and Positron Emission Tomog...mentioning
confidence: 92%